Endothelial cell–cardiomyocyte crosstalk in diabetic cardiomyopathy. Issue 3 (10th June 2016) - Wan, Andrea; Rodrigues, Brian
Abstract: The incidence of diabetes is increasing globally, with cardiovascular disease accounting for a substantial number of diabetes-related deaths. Although atherosclerotic vascular disease is a primary reason for this cardiovascular dysfunction, heart failure in patients with diabetes might also be an outcome of an intrinsic heart muscle malfunction, labelled diabetic cardiomyopathy. Changes in cardiomyocyte metabolism, which encompasses a shift to exclusive fatty acid utilization, are considered a leading stimulus for this cardiomyopathy. In addition to cardiomyocytes, endothelial cells (ECs) make up a significant proportion of the heart, with the majority of ATP generation in these cells provided by glucose. In this review, we will discuss the metabolic machinery that drives energy metabolism in the cardiomyocyte and EC, its breakdown following diabetes, and the research direction necessary to assist in devising novel therapeutic strategies to prevent or delay diabetic heart disease.